Battle of the boss-monster - Cummings, Troy (Cummings, Troy. Notebook of doom, 2018)
In the year since Alexander and his father moved to Stermont, he and his friends in the Super Secret Monster Patrol of Stermont Elementary have defeated all kinds of monsters, but now they face their greatest challenge, the boss-monster who has kidnapped fellow monster fighter Ms. Vanderpants and stolen the Notebook of Doom--and they have to do it before Alexander turns eight and stops being able to see monsters.